Growth factor and cytokine characterization of canine platelet lysate with variable leukocyte concentration, plasma content, and heat-sensitive proteins - Lunardon, Thainá; Sumner, Scarlett M.; Mollabashi, Melikasadat; Darzenta, Nikolia; Davis, Emily; Naskou, Maria C. (Frontiers in Veterinary Science, 2024)
Background: Platelet lysate is an acellular platelet product containing factors released from secretory granules, including cytokines and growth factors. This study aimed to evaluate different centrifugation methods used to prepare canine platelet lysate with variable content of leukocytes, plasma, and heat-sensitive proteins. Methods: Whole blood was collected from six dogs and two double-spin preparation methods were used to generate the platelet-rich plasma with reduced (PRP) and high (L-PRP) concentrations of leukocytes. A portion of both methods underwent plasma depletion via centrifugation and platelet lysate was generated via freeze-thaw cycles. A portion of the generated platelet lysate underwent complement inactivation via heat treatment. Growth factors (TGF-β1, VEGF, TNF-α, PDGF-BB, HGF) were quantified in all different platelet lysate preparations using ELISAs. Results: Both platelet-rich plasma preparations had a 6.7-fold increase in platelet concentration. White blood cell (WBC) concentration compared to whole blood increased 1.2-fold times in PRP and 1.9-fold times in L-PRP. Negligible concentrations of platelets, WBC, and hematocrit were identified in all lysate groups. Statistically significant differences were identified for PDGF, VEGF, and TNF-α, and not for TGF-β or HGF. No growth factor differences were noted between centrifugation methods. PDGF was significantly higher in platelet lysate that was plasma depleted. VEGF was significantly higher in heat-treated lysate groups. TNF-α concentrations were overall very low, though were noted to significantly increase following plasma depletion. Conclusion: These results support that growth factors and cytokine release can be affected by the platelet lysate preparation and processing.